Harnessing parental involvement and educational equity for sustainable development in South African schools - Newlin Marongwe; Godfrey Mutesasira (Interdisciplinary Journal of Sociality Studies)
The importance of parental involvement in schools cannot be overemphasised. Government and donor agencies have recognised the significant role of parents in the educational development of their children. This conceptual paper, therefore, explores how parental involvement can be harnessed to uplift and promote educational equity in South African schools amidst the urgent need for collaborative efforts between parents, schools, and policymakers to mitigate challenges and advance the Sustainable Development Goals (SDGs). Bronfenbrenner's Ecological Systems Theory was used to anchor the study. A typology methodological design was employed to identify and categorise four themes discussed in the paper. Through exploring effective parental in¬volvement strategies, this paper provides actionable insights for enhancing academic outcomes and advancing SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities) within the South African context. Therefore, recognising educational disparities, this paper advocates for a holistic approach to parental involvement that empowers families, strengthens communities, and promotes sustainable development. The paper concludes that parental involvement is a powerful catalyst for educational equity and sustainable development in South African schools. Through collaborative efforts and a commit¬ment to social justice, the transformative potential of parental involvement can be harnessed to build a more equitable and inclusive education system that advances the SDGs and ensures a brighter future for all children in South Africa and beyond.